The Value of Quantitative Faecal Immunochemical Testing as a Prioritisation Tool for the Endoscopic Investigation of Patients With Iron Deficiency - Clackett, William; Barclay, Stephen T.; Stanley, Adrian J.; Cahill, Aidan (Frontiers in Medicine, 2021)
Difficulty in providing endoscopy for patients with iron deficiency anaemia (IDA) during the COVID-19 pandemic has highlighted the requirement for a prioritisation tool. We aimed to test the validity of qFIT as a prioritisation tool in patients with iron deficiency and its ability to identify patients with advanced neoplastic lesions (ANLs). Data collected from patients referred with biochemically proven iron deficiency (ferritin ≤ 15 µg/L) and synchronous qFIT who underwent full gastrointestinal investigation within NHS Greater Glasgow and Clyde was analysed retrospectively. Patients who did not undergo full investigation, defined as gastroscopy and colonoscopy or CT colonography, were excluded. ANLs were defined as defined as upper GI cancer, colonic adenoma over 1cm or colorectal cancer. Area under the curve (AUC) analysis was performed on qFIT results and outcome, defined as the presence of an ANL. AUC analysis guided cut-off scores for qFIT. Patients with a qFIT of <10, 10-200, >200, were allocated a score of 1, 2 and 3 respectively. A total of 575 patients met criteria for inclusion into the study. Overall, qFIT results strongly predicted the presence of ANLs (AUC 0.87, CI 0.81-0.92; P <0.001). The prevalence of ANLs in patients with scores 1 to 3 was 1.2%, 13.5% and 38.9% respectfully. When controlled for other significant variables, patients with a higher qFIT score were statistically more likely to have an ANL (qFIT score = 2; OR 12.8; P<0.001, qFIT score = 3, OR 50.0; P<0.001). A negative qFIT had a high NPV for the presence of ANLs (98.8%, CI 97.0%-99.5%). These results strongly suggest that qFIT has validity as a prognostic tool in patients with iron deficiency; both allowing for a more informed decision of investigation of patients with very low risk of malignancy, and in identifying higher risk patients who may benefit from more urgent endoscopy.